2014
DOI: 10.1007/s00454-014-9621-6
|View full text |Cite
|
Sign up to set email alerts
|

Crackle: The Homology of Noise

Abstract: We study the homology of simplicial complexes built via deterministic rules from a random set of vertices. In particular, we show that, depending on the randomness that generates the vertices, the homology of these complexes can either become trivial as the number n of vertices grows, or can contain more and more complex structures. The different behaviours are consequences of different underlying distributions for the generation of vertices, and we consider three illustrative examples, when the vertices are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 20 publications
1
85
0
Order By: Relevance
“…The study of random simplicial complexes originated in the seminal result of Erdős and Rényi [14] on the phase transition for connectivity in random graphs G(n, p) (with n vertices, and where edges are included independently and with probability p) . In their paper, Erdős and Rényi studied these graphs in the limit when n → ∞ and p = p(n) → 0, and showed that the phase transition for connectivity occurs around p = log n∕n, when the expected degree is approximately log n. 1 Over the past process on M with intensity n (see definition in Section 2.3). With no loss of generality, and to shorten notation, we will assume that Vol(M) = 1 as this will only affect the results by an overall scaling constant.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of random simplicial complexes originated in the seminal result of Erdős and Rényi [14] on the phase transition for connectivity in random graphs G(n, p) (with n vertices, and where edges are included independently and with probability p) . In their paper, Erdős and Rényi studied these graphs in the limit when n → ∞ and p = p(n) → 0, and showed that the phase transition for connectivity occurs around p = log n∕n, when the expected degree is approximately log n. 1 Over the past process on M with intensity n (see definition in Section 2.3). With no loss of generality, and to shorten notation, we will assume that Vol(M) = 1 as this will only affect the results by an overall scaling constant.…”
Section: Motivationmentioning
confidence: 99%
“…The proof of Theorem 1.1, has a similar outline to the one in [7], but with considerable geometric adjustments required for the Riemannian case. In fact, the approach we use here for addressing the general setting turns out to be powerful by allowing us to (1) weaken some of the conditions required in [7], and (2) prove many other statements for randomČech complexes in the Riemannian setting.…”
Section: Outline Of the Proofmentioning
confidence: 99%
See 3 more Smart Citations